Identity of Roma women and processes of international and transitional justice - Jara Gómez, Ana María (The Age of Human Rights Journal, 2021)
Among the women involved in international legal environments, there are women who are administrators of justice, and women who remain as recipients, consumers or petitioners of justice. The question of identity, be it national, cultural, ethnic, religious or otherwise may become crucial when positioning human beings in one side of justice or another. This article seeks to analyse the formation of identities and the characteristics of Roma women’s identity and specifically their roles in international justice together with some actual European political stances towards the Roma peoples. Part of the study will take into account the sequence of processes that take place from the appointment of international judges to the resolutions of the United Nations Security Council, and that lead to the granting of a certain place for women in the transitional/international justice scene. Nevertheless, there are also groups of women who hardly participate in the international legal scene and, although their role has historically been, and still is, reduced to being victims, their possibilities of action in the field justice are extraordinarily limited. This is the case of Roma women in Europe.